La filosofia dell'immaginazione in Vico e Malebranche - Paolo, Fabiani (Scuole di dottorato, 2002)
The book, which is a redrafting of the doctoral thesis, represents a retrospective on modern philosophical anthropology through two of its major exponents. More specifically, it shows how mythology, the history of philosophy and language and Vico's conception of man have had as a constant yardstick the Cartesian approach of the psychology of Malebranche.